Comparison of surgical resection of Axillary Lymph Nodes in Dogs with Mammary Gland Tumors with or without sentinel lymph node visualization with patent blue dye - Souza, Mayara Coutinho Carlo de; Flecher, Mayra Cunha; Arrais, Fernanda Ming; Sena, Bruna Voltolin de; Giuliano, Antonio; Horta, Rodrigo dos Santos (Frontiers in Veterinary Science, 2023)
Introduction: Dogs’ axillary lymph node (ALN) is often difficult to locate before surgical resection. The anatomical location of ALN often discourages Veterinarians from surgical lymphadenectomy. Considering the limited literature available, the actual incidence of metastases and the prognostic relevance are poorly understood. Methods: A non-randomized, prospective clinical study was conducted with female dogs (n = 41) with mammary gland tumor (MGT) in the thoracic or cranial abdominal mammary glands. The study investigated the risks of ALN metastasis based on tumors clinical findings, tumor size, histopathological diagnosis and grade. The main aim of this study was to compare ALN resection with or without patent blue 2.5% (PB) dye injection for sentinel lymph node visualization. A total of 46 mastectomies were performed and five animals underwent two mastectomies. In the first group, 17 patients underwent a mastectomy and lymphadenectomy without PB injection (G1). In contrast, in the second group, 24 patients also received PB injections for sentinel lymph node mapping (G2). The ALN was identified in 38/46 cases (82%). The ALN was identified and excised in only 58% of surgeries in G1(19/46), while in group 2, the lymph node was identified in 92% of the cases and resected in 100% of the cases. The use of PB improves ALN’s identification and reduces the surgical resection time in dogs with MGT. Results and discussion: Surgical time differed between the two groups, as it was significantly shorter in the PB injection group compared to group 1 (80 vs. 45 min) (p < 0.0001). The overall frequency of ALN metastasis was 32%. Macroscopic abnormalities in the lymph nodes, tumor size (>3 cm), and diagnosis of anaplastic carcinoma or grade II/III mammary gland tumors were associated with a higher probability of ALN metastasis. Metastases in the ALNs are more common, in dogs presenting with tumors larger than 3 cm and diagnosed with aggressive histological subtypes. The ALNs should be removed for correct staging, prognostic evaluation, and decision for adjuvant therapy.